Seizure Assessment for Driving License Medical Certification in Thailand - Pattaramongkolchai, Sutpattida; Chamroonsawasdi, Nattanand (Disease Control Journal, 2026)
Epilepsy is a significant health condition that increases the risk of traffic accidents by approximately 1.13 to 2.13 times compared with the general population and accounts for about 0.2 percent of traffic-related fatalities. Consequently, seizure disorders are recognized as a condition requiring thorough health evaluation prior to the issuance of a driving license. This narrative review aimed to examine information on seizure characteristics, health assessment procedures, and appropriate seizure-free intervals for granting driving privileges across different types of seizures and vehicle categories, with a comparative analysis between Thai regulations and international practice guidelines. Findings from the review indicated that Thailand currently mandates a seizure-free period of more than one year before individuals with epilepsy are permitted to drive. This requirement corresponds to an acceptable annual risk of sudden incapacity of approximately 20 percent. In contrast, international authorities delineate seizure-free intervals based on both seizure type and driving category to minimize the risk of sudden incapacitation among private and commercial drivers. The authors propose that seizure assessment should include a comprehensive medical history, physical examination, and evaluation of sensory, motor, and cognitive functions to establish a probable diagnosis. Furthermore, it is recommended that a 10-year seizure-free period be required for individuals with epilepsy seeking to drive commercial vehicles. The specific seizure-free duration applicable to each vehicle category should also be clearly stated in the medical certificate for driving authorization. These measures aim to help reduce accidents, minimize losses, lower medical expenses, and enhance safety standards through stricter health-related regulations.